Impact of the Salary Scale for Key Actors in Public Learning Institutions on the Right to Education - Elvis Ntege (Uganda Christian University, 2024)
Salary is a key aspect for work performance irrespective of professional conduct

It is a reality truth that salaries are a precondition for employee work performance regardless of professional identity anywhere in the world. Correspondent to the title, it proposes scrutinizing the efficacy of key players in public learning institutions within Uganda that is to say teachers, school board members, administrators and government officials in proselytizing the right to education. The salient objective of this research is to uncloak the suffrage of students as key stakeholders of the education service in Uganda based on the unaccredited concerns as to the remuneration for quintessential actors in our education system. The data at hand emerges from research conducted using secondary sources available online and textbooks. Subject to this research, it envisages an assessment of quality time spent fulfilling educational responsibilities in comparison with the period taken in other subsidiary financial engagements. Findings on the impact of the salary scale for key players in public institutions of learning within Uganda on the right to education illustrate that salaries of intrinsic actors in public institutions of learning are predominant on the actualization of the right to education.